Bibliometrics Analysis of Digital Technology in Entrepreneurship - Fareeda Nafeesa; Irfana Shakira; A Chaithra; Shruthi (ITM Web of Conferences, 2024)
Digital technologies are frequently used in business, particularly for product advertising, sales, marketing, operations management, and improved customer service. This study used bibliometric visualization to map the position of digital technology in worldwide entrepreneurship studies published and indexed by the Web of Science. Bibliometric methodologies and research data analysis were carried out using the VOS viewer application’s analysis search results service and the Web of Science. The Web of Science database included research data for 558 documents published between 2015 and 2024. The findings revealed that England, People R China, Finland, France, and Sweden were the most productive nations, with institutional affiliations, and individuals publishing digital technology in entrepreneurship studies. Most document categories and subject areas in digital technology in entrepreneurship studies were openaccess documents. The findings highlight significant contributions to entrepreneurship by advancing the literature and highlighting key research fronts, offering insights that previous reviews still needed to fully grasp. The analysis and graphical displays provide valuable insights into how digitization affects entrepreneurship. The topic’s novelty and the gap revealed in previous research on digital technology on entrepreneurship prompted us to take an integrated strategy that included bibliometric analysis.